Peran IPS Sebagai Upaya Pengembangan Kebudayaan Terhadap Peserta Didik - Rizki, Rizki Sofyan Rizal; Abdul L, Nuchayani; Ediyanto; Zusril W, Muhammad (CV. Supernova Office Stationary and Printing, 2023)
Social Sciences (IPS) is an educational program that has educational materials from various social and human science disciplines (education and history) which are organized and presented scientifically and psychologically for educational purposes based on Pancasila and Indonesian Culture. Social studies can also be said to be a fusion or combination of a number of social subjects so that the social studies subjects use certain parts of the social sciences. In principle, social studies education in elementary schools does not teach social sciences as a scientific discipline, but rather the essential concepts of social sciences to shape students into good citizens. Social studies as a subject that plays a significant role in developing culture is expected to empower and make the best use of the available local culture. Social studies learning in elementary schools is expected to develop various abilities in students, especially the ability to live in the environment or community where students live. Therefore, teachers are needed who have an adequate understanding of local cultural values, in addition to the ability to understand the subject matter for which they are responsible. The creation of culture cannot be separated from the process of social interaction, whether between individuals, between groups, or individuals and groups. Social interaction is the most real reality in human life.